The Limits of Subtraction. Issue 2 (3rd April 2017) - Colyvan, Mark
ABSTRACT: In the target article 'If-Thenism', Stephen Yablo develops a novel form of if-thenism, that appeals to the notion of logical subtraction. In this commentary, I explore the limits of Yablo's proposed subtraction procedure, by leaning on an analogy with photographic subtraction. In particular, I will argue that there will be cases when there's nothing interesting left after the subtraction (a possibility Yablo himself raises) and, as a consequence, there are serious limits to the applicability of the subtraction procedure.